The Mediating Role of Empowering Workers in the Relationship Between Strategic Leadership Practices and Strategic Alignment : A Study in Medium and Small Sized Companies in Kirkuk - Abdulazeez Mohammed Alwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The research aims to test the mediating role to enable workers to test the relationship between strategic leadership practices and strategic alignment in medium and small-sized companies in the Iraqi city of Kirkuk, and to achieve that goal and to solve the research problem and take advantage of its importance, a field visit was conducted for the companies of the study sample to see the reality of their work regarding the research variables, and then a questionnaire form was designed according to the five-point Likert scale and distributed to a sample of (369) workers representing the companies of the study sample to collect data and information, and analyze those Statistical program usage data (SPSS, AMOS) V26 In light of these results, the research revealed that there is a statistically significant impact relationship for strategic leadership in strategic alignment through the mediation of empowering workers in medium and small-sized companies in Kirkuk, and accordingly a set of recommendations were made, the most important of which was the need to work to improve organizational performance and enhance competitiveness of companies through the application of best strategic leadership practices, empowering employees and achieving strategic alignment in the surveyed companies.